Capability of Building Information Modeling Application in Quantity Surveying Practice - Phui Fung, Wong; Salleh, Hafez; Mohd Rahim, Faizul Azli (Journal of Surveying, Construction and Property, 2014)
Building information modeling (BIM) application has the potential to revolutionize the quantity surveying practice. It appears that quantity surveyors are still lagging behind in BIM application compared to other professionals. Low adoption among quantity surveyors is due to lack of awareness of the potential of BIM application toward their profession. Quantity surveyors are still unsure of the capability of BIM in their practice. It is still generally underexplored how BIM application contributes to quantity surveyors performance improvement. This research attempts to identify the capabilities of BIM application in quantity surveying practice to increase awareness. The scope of this research limited to pre-construction stage. The potential capabilities are found through literatures and verify through interviews with eight quantity surveyors till achieve saturation. The findings indicated that there are 11 potential BIM capabilities that can enhance quantity surveyors’ performance and majorities of them are confirmed by the interviewees. These findings provide clear understanding that BIM application has the capabilities to enhance quantity surveyors’ performance where traditionally their works are known as time-consuming and error-prone.